Dénombrement Des Populations Naturelles De Rhizobium Du Pois Chiche (Cicer Arietinum) Dans Différents Sols Du Maroc - Machehouri Abdelkader; Ben Messaoud Btissam; Nassiri Laila; Ibijbijen Jamal (European Scientific Journal, ESJ, 2017)
For the legumes cultivation, the presence of specific Rhizobium in the soil is very necessary in fact a minimum number of bacteria is essential to obtain a good nodulation. The formula used for the count of Rhizobia in soil is the most probable number (MPN) method. For this purpose, four cultivation systems were used: d1, d2, d3 and d4. The soils of the all studied regions have a natural population of Rhizobium sp cicer. The size of this population is determined by the MPN method. This has been attributed to the use of plant growth systems. The result have shown that just the cultivation system d1 will be considered to realize such studies even that this system have shown some failure. Moreover, the MPN method failed on the evaluation of the rhizobia population hence the need to find a new specialized method.